Pequeno mapa do tempo de crise: ensino de história, afetos e negacionismos na era digital - Oliveira, André Fialho de (2023)
Starting from the research line “Languages and Historical Narratives: Production and Dissemination”, this work sought to map elements that compose the situation of disorientation claimed in the recent debate between history teaching and theory, tracing layers of what can be understood as a transversal crisis, in the face of the transformations of the process of plataformization and neoliberalization in the first two decades of the 21st century. From a game of scales, from the disciplinary to the temporalization of a time of permanent crisis, this work has mapped the forces that compose this phenomenon, associating it to the formulation and popularization of new forms of historical negationism. To better understand them in their relation to the anti-structural dynamics of digital platforms, it was based on Baruch de Spinoza’s affect theory and its re-reading by Gilles Deleuze and Félix Guattari, as well as on recent studies of cybernetic-inspired digital anthropology by Letícia Cesarino, when emphasizing the concept of resentment in the affective dimension of political disputes. Finally, after an empirical analysis of production, circulation and consumption of historical narratives by digital publics, based on a survey of social network sources, this paper proposed experimental directions for teaching practice, under the name of “teaching through wandering”, as part of the ethical-political turn that recently has moved history discipline.